MicroRNA-9 Enhanced Cisplatin Sensitivity in Nonsmall Cell Lung Cancer Cells by Regulating Eukaryotic Translation Initiation Factor 5A2. (5th August 2018) - Pan, Qiaoling; Sun, Lebo; Zheng, Dawei; Li, Ni; Shi, Huoshun; Song, Jie; Shao, Guofeng; Xu, Guodong
Abstract : We determined the role of microRNA (miR)-9 in regulating cisplatin chemoresistance in nonsmall cell lung cancer (NSCLC) cells. miR-9 and eukaryotic translation initiation factor 5A2 (eIF5A2) levels were examined by reverse transcription–quantitative PCR. Cell Counting Kit-8 and the 5-ethynyl-2′-deoxyuridine (EdU) assay were used to determine the effects of miR-9 mimic or inhibitor on NSCLC cell proliferation and viability, respectively. Bioinformatics was used to analyze the relationship between miR-9 and eIF5A2. Flow cytometry was used to analyze the percentage of apoptotic cells. miR-9 mimic enhanced cisplatin sensitivity, while miR-9 inhibitor produced the opposite result. eIF5A2 was identified as a potential target of miR-9, where miR-9 regulated eIF5A2 expression at mRNA and protein level. miR-9 mimic decreased the expression of eIF5A2 mRNA and protein, while miR-9 inhibitor increased eIF5A2 expression. eIF5A2 knockdown resolved the effects of miR-9 mimic or inhibitor on cisplatin sensitivity. miR-9 may be a potential biomarker for enhancing cisplatin sensitivity by regulating eIF5A2 in NSCLC cells.